KORELASI ANTARA PUASA SUNNAH SENIN KAMIS DENGAN STABILITAS EMOSI MAHASANTRI INTENSIF PUTRI INSTITUT DIROSAT ISLAMIYAH AL-AMIEN PRENDUAN - Khotijah, Sitti; Arica, Via Naila (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Sunnah fasting of monday and thursday is one method or way of Muslims to control lust. Because as in the adab of fasting, all actions and speech will be far from all forms of noise, lies and cunning. This study is to determine the relationship between sunnah fasting of Monday and thursday by emotional stability of female mahasantri, especially the intensive program Institute of Dirosat Islamiyah Al-Amien Prenduan. The research method used in this study uses quantitative research methods, with data collection techniques using questionnaire methods and observation methods. To analyze the data, researchers used statistical techniques by product moment correlation formula. With a sample using 92 respondents. Based on the calculation results of the product moment correlation formula, that the relationship between Sunnah fasting of monday and thursday by emotional stability mahasantri amounted to 74.4%, while for the rest is not discussed in this study. It can be concluded that there is a correlation between Sunnah fasting of monday and thursday by emotional stability of intensive female mahasantri Institute of Dirosat Islamiyah Al-Amien Prenduan.